Rapid assessment of avoidable blindness in the Occupied Palestinian Territories. - Far Chiang (Public Library of Science (PLoS), 2010)
Background There are no recent data on the prevalence and causes of blindness in the Occupied Palestinian Territories. The aim of our study was to estimate the prevalence and causes of blindness and visual impairment in the population aged 50 years and above in the Occupied Palestinian Territories using the Rapid Assessment of Avoidable Blindness (RAAB) survey method. Methods and findings Clusters of 40 people who were 50 years and above were selected with probability proportionate to size using a multistage cluster random sampling method. Participants received a comprehensive ophthalmic examination in their homes, including visual acuity testing by one of three experienced ophthalmologists. The principal cause for visual loss was determined by an experienced ophthalmologist using portable diagnostic instruments. Information about previous cataract surgery, satisfaction with surgery and barriers to cataract surgery were collected. The prevalence of self-reported diabetes was also determined. The prevalence of bilateral blindness (VA<3/60 in the better eye with available correction) was 3.4% (95% CI: 2.7-4.0), 2.0% (95% CI: 1.4-2.5) for severe visual impairment (VA>or=3/60 and <6/60), and 7.4% (95% CI: 6.4-8.3) for visual impairment (VA>or=6/60 and <6/18). Avoidable causes (i.e. cataract, refractive error, aphakia, surgical complications, corneal scarring and phthysis) accounted for 80.0% of bilateral blindness, severe visual impairment (70.7%) and visual impairment (86.2%). Cataract was the main cause of blindness (55.0%). The prevalence of blindness was higher in Gaza (4.9%, 95% CI: 3.7-6.1%) than in the West Bank (2.5%, 95% CI: 1.9-3.1%) and among women (4.3%,95% CI: 3.3-5.2%) compared to men (2.2%,95%CI:1.5-2.9%). Among people who had undergone cataract surgery in the past, only 54.5% of eyes obtained a good outcome (VA>or=6/18), 23.2% had a borderline outcome (VA<6/18 and >or=6/60) and 22.3% had a poor outcome (VA<6/60) with available correction. The prevalence of self-reported diabetes mellitus in >or=50 year age group was 26.4% (95% CI: 24.9-27.9). Conclusions The prevalence of blindness suggests that significant numbers of people in the Occupied Palestinian Territories exist who do not access eye care - predominantly women and those residing in Gaza. Programmes need to focus on maximizing the use of current services by these excluded groups.